Combined Assessment of Gastrointestinal Hormones and Metabolomic Profiling Following Mixed-Meal Tolerance Tests in Patients at Increased Risk of Refeeding Syndrome: Study Protocol - Gonçalo Nunes; Marta Guimarães; Sofia S. Pereira; Ivo Mendes; Francisco Vara-Luiz; Cátia Oliveira; Marta Gonçalves; Patrícia Mendes; Rute Santos; Tânia Meira; Jorge Fonseca (Journal of Personalized Medicine, 2026)
Introduction: Refeeding syndrome (RS) is a life-threatening metabolic complication of nutritional support. Prolonged fasting, frequently observed in malnourished patients referred for percutaneous endoscopic gastrostomy (PEG), may induce histological and ultrastructural changes in the intestinal mucosa, potentially influencing metabolic adaptation during nutritional reintroduction. Mixed-Meal Tolerance Tests (MMTT) combined with targeted metabolic profiling allow dynamic assessment of serum glucose, gastrointestinal hormones and metabolites, which may help to elucidate the metabolic adaptations associated with fasting and refeeding. Objective: The present study aims to perform MMTT in PEG patients to characterize enteroendocrine hormone responses and metabolomic profiles following a prolonged period of reduced nutritional intake and subsequent enteral refeeding. Methods: This prospective, single-center study includes adults referred for PEG after at least one month of oral intake below 50% of energy needs. The MMTT will be performed at PEG placement and after 3–6 months of enteral nutrition. Serial blood samples will be collected from baseline up to 120 minutes post-meal to measure serum glucose, insulin, C-peptide, electrolytes and gastrointestinal hormones (GLP-1, GIP, ghrelin and PYY), and for targeted metabolomic profiling by spectroscopy. Clinical and nutritional data will be prospectively recorded. Exploratory analyses will assess metabolic and hormonal changes over time and their potential associations with relevant clinical characteristics. The study was approved by the institutional ethics committee, and patient informed consent will be obtained. Conclusion: This study integrates MMTT and targeted metabolomic profiling to characterize hormonal and metabolic responses during fasting and refeeding in PEG patients considered at increased risk of RS due to prolonged markedly reduced oral intake. The findings may improve understanding of metabolic adaptations associated with nutritional reintroduction and may identify candidate hormonal and metabolic signatures to support future studies on RS pathophysiology and risk assessment.